The evolution of mating‐type switching for reproductive assurance. (21st September 2016) - Nieuwenhuis, Bart P. S.; Immler, Simone
Abstract : Alternative ways to ensure mate compatibility, such as hermaphroditism and the breakdown of self‐incompatibility, evolved repeatedly when finding a mating partner is difficult. In a variety of microorganisms where compatibility is determined by mating‐types, a highly regulated form of universal compatibility system called mating‐type switching has evolved several times. This sophisticated system allows for the genetic adjustment of the mating type during asexual growth, and it most likely evolved for reproductive assurance of immotile species under low densities. In this review, we compare the switching strategy to other universal compatibility systems such as "unisexual mating" and homothallism. We identify the costs of switching, including genome instability, and mechanistic costs, as well as the benefits, mainly the maintenance of important mating‐type functions. Given the potential benefits of mating‐type switching, we speculate that switching is likely to have evolved many times independently, and may be more common in groups where genetic mating types regulate mate compatibility than assumed so far. Abstract : Mating in microorganisms is only possible between cells of opposite mating types. If suitable mating partners are rare, mating‐type switching through rearrangements at the genomic level may evolve as a mechanism to ensure reproduction. We discuss the possible costs and benefits leading to the evolution of mating type switching.